Analisis Hubungan Penggunaan Antibiotik dengan Lama Terapi Pasien Anak Diare Akut di RSUD Soedirman - Ainni, Ayu Nissa; Khuluq , Muh. Husnul; Nisa, Isnaeni Al Khoerotun (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Acute diarrhea remains a major problem causing the second highest mortality rate for children in Indonesia. One of the therapies used for acute diarrhea with infection is the administration of antibiotics. If the use of antibiotics is not rational, it will cause high side effects, longer patient treatment, affecting the high cost of hospitals and decreasing the quality of hospital services. The purpose of this study is to analyze the relationship between antibiotic use and treatment duration in order to reduce irrationality and shorten treatment duration in hospitals. The research method used is qualitative research with a correlation study design, with retrospective data collection from January to December 2022. Medical record data of patients, including the type of antibiotic and length of treatment for acute diarrhea in children with bacterial infections in the inpatient ward of RSUD dr. Soedirman, were used as research material. The data obtained were then analyzed using the Gamma correlation test using SPSS version 20. The results of this study showed that almost all patients (100%) received antibiotics and Ceftriaxone (54.29%) was the most prescribed antibiotic, both in single and combination forms. The longest treatment duration for acute diarrhea in children with antibiotics was 4 to 5 days (58.57%). The Gamma correlation test showed that the use of antibiotics and treatment duration had a significance value of 0.000 (<0.005). The use of antibiotics given to children with acute diarrhea has a significant relationship with treatment duration at RSUD dr. Soedirman.